A predator prey model with Fuzzy initial populations - Muhammad Zaini, Ahmad; Bernard, De Baets (International Fuzzy Systems Association and European Society for Fuzzy Logic and Technology, 2009)
Organized by International Fuzzy Systems Association and European Society for Fuzzy Logic and Technology, 20th - 24th July 2009 in Lisbon, Portugal.